2006
DOI: 10.1590/s0100-736x2006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Sazonalidade de Haematobia irritans no Brasil Central

Abstract: Horn fly (Haematobia irritans) is one of the most important Brazilian cattle ectoparasites. Epidemiological studies are needed due the increasing difficulty of their chemical control. In order to obtain a better knowledge of their seasonal population dynamics, 14 days interval fly counts were made on 7-30 month old beef cattle, from winter 1996 to summer 2002. Horn fly population levels increase (P<0.05) was observed during the seasons of each infestation period (spring until autumn), mainly in spring and summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
2
4
0
7
Order By: Relevance
“…Lima et al (2002) Nevertheless, horn fly infestation was observed throughout the year, with two infestation peaks (Figure 1), in April (also June) and October/November, coinciding with the end (autumn) and the beginning (spring) of the rainy season, respectively. Similar results were found by Lima et al (2003), in Araçatuba, SP; Barros (2001), in the Pantanal region, MS; and Bianchin et al (2006), in Campo Grande, MS.…”
Section: Resultssupporting
confidence: 85%
“…Lima et al (2002) Nevertheless, horn fly infestation was observed throughout the year, with two infestation peaks (Figure 1), in April (also June) and October/November, coinciding with the end (autumn) and the beginning (spring) of the rainy season, respectively. Similar results were found by Lima et al (2003), in Araçatuba, SP; Barros (2001), in the Pantanal region, MS; and Bianchin et al (2006), in Campo Grande, MS.…”
Section: Resultssupporting
confidence: 85%
“…Horn fly infestations showed features similar to those observed in previous studies conducted in the region (BIANCHIN; ALVES, 2002;BIANCHIN et al, 2006). The mean number of infestations was low between May and October (x = 5 to 40) of both cycles, peaking in November and December (x = 160 and 170) of the first cycle and in November and April (x = 190 and 110) of the second cycle.…”
Section: Parasitological Datasupporting
confidence: 83%
“…The highest mean RH occurred during the rainy season, which might have influenced the blood concentration of cortisol because RH favours the occurrence of ectoparasites such as haematophagous insects that disturb the animals, cause them stress, and interfere negatively with their metabolic processes (Bianchin et al, 2006).…”
Section: Resultsmentioning
confidence: 99%